Pelatihan Penyusunan Modul Ajar Berbasis Augmented Reality Bermuatan Nilai Karakter Pancasila Untuk Guru Bahasa Indonesia Mts Se-Kota Cirebon - Veni Nurpadillah; Emah Khuzaemah; Inggit Nurul Istifaedah (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
TRAINING FOR PREPARING AUGMENTED REALITY-BASED TEACHING MODULES CONTAINING PANCASILA CHARACTER VALUES FOR MTS INDONESIAN LANGUAGE TEACHERS IN THE CITY OF CIREBON. Teaching modules and learning media are learning tools that must be prepared. One of the interactive learning media based on information and communication technology is Augmented Reality (AR). The use of augmented reality in learning that contains the Pancasila Character Values provides a more fun and interactive learning experience for students. In view of the problems of teachers who still experience difficulties in compiling teaching modules that suit students' needs, with the existence of PkM related to "Training on Preparing Augmented Reality Video-Based Teaching Modules Containing Pancasila Values for Indonesian Language Teachers at MTs throughout Cirebon City" aims to provide a forum for teachers to help prepare augmented reality video teaching materials containing Pancasila values. This activity has several stages, from observation, document analysis, carrying out training, assistance in preparing teaching modules, monitoring to evaluation. The results of PkM can be said to have been able to develop teaching modules in accordance with the expectations of the independent curriculum. However, there are teachers who are still unable to create media or teaching materials that utilize the Augmented Reality application, this is due to several factors, one of which is that MTs teachers are senior teachers so they are less technologically literate, this does not dampen the enthusiasm of teachers to use it. augmented reality application that we have provided in learning.